(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, we will focus on the works of the Victorian Age, which is considered one of the most productive periods of English literature, and the works of feminist writers who lived and contributed in this period, including Bronte sisters especially Charlotte Bronte, Elizabeth Gaskell, and George Eliot.